Reviewed Study on Non-Statutory and Statutory Indian Labor Welfare Schemes: Exploring Labor Welfare Measures in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ancient Indian Literature ‘Manusmrithi’ mentioned about codes for the protection and safety of the people. The concept of Social Security was associated with the Hindu Joint Families which was the ‘Original Cell of Security’ and ‘First Line of Defense’ against any misfortune. Then in Vedic period ‘Guilds’a group of merchants or artisans worked during calamities for the security of life and property. Organized Social Security Measures in statutory form are of recent origin as a key factor in Industrial system to protect employees and their dependents against contingencies like disability, sickness, employment injury and unemployment. The Schemes for Provident Fund, Medical Insurance, Maternity Benefit, Compensation and Gratuity are useful in India. The efficiency, extent of coverage, finding suitable policy and approaches to strengthen the delivery system according to priorities through planned justice for inclusive growth is the need of the day. This article is a reviewed study to understand Labor Welfare measures and non-statutory and statutory Indian labor welfare schemes related to it.